2021
DOI: 10.3390/polym13224001
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Polymer Nanocomposites Subjected to Uniaxial Extension: A Nonequilibrium Molecular Dynamics Study

Abstract: We explore the behavior of coarse-grained ionic polymer nanocomposites (IPNCs) under uniaxial extension up to 800% strain by means of nonequilibrium molecular dynamics simulations. We observe a simultaneous increase of stiffness and toughness of the IPNCs upon increasing the engineering strain rate, in agreement with experimental observations. We reveal that the excellent toughness of the IPNCs originates from the electrostatic interaction between polymers and nanoparticles, and that it is not due to the mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The excellent toughness of the ionic nanocomposites was shown to originate from the electrostatic interaction between ionic polymers and nanoparticles, and was not due to the nanoparticles mobility, as was speculated in Ref. [ 58 ] or the presence of polymer–polymer entanglements [ 150 ].…”
Section: Simulationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The excellent toughness of the ionic nanocomposites was shown to originate from the electrostatic interaction between ionic polymers and nanoparticles, and was not due to the nanoparticles mobility, as was speculated in Ref. [ 58 ] or the presence of polymer–polymer entanglements [ 150 ].…”
Section: Simulationsmentioning
confidence: 83%
“…Coarse-grained nonequilibrium molecular dynamics (NEMD) simulations [ 150 ] investigated the mechanical response of ionic nanocomposites for polymers carrying charges on every third monomer and of different dielectric constant, that influenced the electrostatic strength (via Bjerrum length). An increase in stiffness and toughness of the ionic nanocomposites was observed upon increasing the engineering extensional strain rate, as can be seen in Figure 20 , and in agreement with experimental observations [ 58 ].…”
Section: Simulationsmentioning
confidence: 99%
“…Furthermore, numerical studies allow gaining a deeper insight into new materials without expensive experiments. Moghimikheirabadi et al investigate the mechanical behavior of novel ionic polymer composites and reveal through MD simulations that the complex microstructure of the polymer has a decisive influence on the overall strength [24].…”
Section: Introduction and Previous Work 1interphases And Size Effects...mentioning
confidence: 99%
“…Various simulation studies have been conducted to clarify the thermomechanical properties of polymers [21][22][23][24], reinforcements [25,26], and composites [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] using MD simulations. For composites of thermosetting polymers and carbon-nanotubes (CNT), Alien et al and Park et al conducted pullout tests to investigate the effect of the atomisticscale mechanism on the interfacial shear modulus [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…They found that CGMD can reproduce the interfacial properties by adjusting the parameter of Lennard-Jones potential and the degree of course-graining. Moghimikherabadi et al showed the electrostatic interaction improves the stiffness and toughness of ionic polymer nanocomposites using CGMD [40]. Karatasos and Kritikos performed a full-atomic MD simulation for the graphene oxide/poly(acrylic acid)nanocomposite [41].…”
Section: Introductionmentioning
confidence: 99%